Non-Extensive Fragmentation of Natural Products and Pharmacophore-Based Virtual Screening as a Practical Approach to Identify Novel Promising Chemical Scaffolds - Vásquez, Andrés Felipe; Muñoz, Alejandro Reyes; Duitama, Jorge; González Barrios, Andrés (Frontiers in Chemistry, 2021)
Fragment-based drug design (FBDD) and pharmacophore modeling have proven to be efficient tools to discover novel drugs. However, these approaches may become limited if the collection of fragments is highly repetitive, poorly diverse, or excessively simple. Here we demonstrated that combining pharmacophore modeling and a non-classical type of fragmentation (herein called non-extensive) to screen a natural product (NP) library may provide fragments predicted as potent, diverse, and developable. Initially, we applied RECAP (retrosynthetic combinatorial analysis procedure) rules in two versions, extensive and non-extensive, in order to deconstruct a virtual library of NPs formed by the databases TCM (Traditional Chinese Medicine), AfroDb (African Medicinal Plants Database), NuBBE (Nuclei of Bioassays, Biosynthesis, and Ecophysiology of Natural Products), and UEFS (Universidade Estadual de Feira de Santana). We then developed a virtual screening (VS) using the two groups of natural-product-derived fragments (extensive and non-extensive NPDFs) and two overlapping pharmacophore models for each of 20 different proteins of therapeutic interest. Molecular weight, lipophilicity, and molecular complexity were estimated and compared for both types of NPDFs (and their original NPs) before and after the VS proceedings. As a result, we found that non-extensive NPDFs exhibited a much higher number of chemical entities compared to extensive NPDFs (45355 vs 11525 compounds), accounting for the larger part of the hits recovered and being far less repetitive than extensive NPDFs. The structural diversity of both types of NPDFs and the NPs was shown to slightly diminish after VS procedures. Finally, and most interesting, the pharmacophore fit score of the non-extensive NPDFs proved not only to be higher, on average, with respect to extensive NPDFs (56% of cases), but also higher than their original NPs (69% of cases) when all of them were also recognized as hits after the VS. The findings obtained in this study indicated that the proposed cascade approach was useful to enhance the probability of identifying innovative chemical scaffolds, which deserve further development to become drug-sized candidate compounds. We consider that the knowledge about the deconstruction degree required to produce NPDFs of interest represents an advantageous starting point for eventual synthesis, characterization, and biological activity studies.